Evapotranspiration and crop coefficients in two irrigated wheat cultivars - Tonny J. A. da Silva; Edna M. Bonfim-Silva; William Fenner; Thiago F. Duarte; Jefferson V. José; Thiago H. F. M. Castañon (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT In the state of Mato Grosso, Brazil, wheat is an alternative to the current production system, mainly in irrigated crops, with new cultivars improved for this environment and system. The objective was to determine the evapotranspiration of the irrigated wheat crop and the dual coefficients of cultivars for the Brazilian Midwest. The experiment was conducted in the field using 12 weighing lysimeters and mini-lysimeters, filled by soil monoliths. The wheat cultivars BRS-254 and BRS-394 were used in the first and second years, respectively. Reference evapotranspiration was obtained by the Penman-Monteith equation and crop evapotranspiration by the mass difference in the lysimeters. Basal crop coefficient and soil water evaporation coefficient were determined according to the crop development stages in both years of cultivation. The mean ETc and ETo values were 3.87, 3.49 mm d-1 and 4.10 and 3.23 mm d-1, respectively, in the first and second cultivation cycles, with higher values of ETc recorded in the reproductive stages of the crop, flowering and grain filling. The basal crop coefficients and soil water evaporation coefficients estimated by weighing lysimeters composed of soil monoliths are: Kcb - 0.42, 0.78, 0.94, 0.74 and 0.47 and Ke - 0.72, 0.52, 0.39, 0.58 and 0.13 for the cultivar BRS-254, and Kcb - 0.28, 0.27, 0.65, 0.98 and 0.66 and Ke - 1.04, 0.96, 0.65, 0.34 and 0.51 for the cultivar BRS-394, at the stages of emergence, tillering, flowering, maturation and harvest, respectively.